EFFICIENCY IN HR: LEAN MANAGEMENT WITH E-SEP AND AUTO CLOSING SYSTEM IN PASAR MINGGU HOSPITAL - Husna, Melanie; Syahputra, Prima (UI Scholars Hub, 2024)
The study focuses on enhancing efficiency in outpatient transactions at Pasar Minggu Hospital, which, in 2019, experienced a high volume of visits primarily covered by national health insurance. With 299,041 outpatient visits using national health insurance that year, the hospital's transition to a COVID-19 referral facility in 2020 underscored the urgency of streamlining operations. Presently, outpatient transactions are manually closed by three staff members, led by the financial administrator, who handles Participant Eligibility Letter files, resolves transaction issues, and finalizes services. Given the imperative for digitization accelerated by the pandemic, the study adopts lean thinking, employing a value stream map (VSM) to identify and optimize value-added activities. Interventions include implementing an electronic Participant Eligibility Letter system and a transaction auto-closing mechanism. The findings indicate a substantial reduction in human resource requirements by two personnel and a streamlined process, saving up to 67 minutes. Besides, this intervention solved two main problems such as the potential of missing manual SEP files and very long transaction in financial administration. This research highlights the efficacy of lean management principles, emphasizing the importance of hospital information system enhancements for outpatient services. By leveraging electronic documentation and automated processes, Pasar Minggu Hospital demonstrates a tangible improvement in operational efficiency amidst evolving healthcare demands.